Legionella longbeachae wound infection: case report and review of reported Legionella wound infections - Frostadottir, Drifa; Wasserstrom, Lisa; Lundén, Karolin; Dahlin, Lars B. (Frontiers in Cellular and Infection Microbiology, 2023)
Extrapulmonary manifestations of infection with Legionella species, of which 24 may cause disease in humans, are very rare. Here, we describe a case of a 61-year-old woman with no history of immunosuppression, presenting with pain and swelling of her index finger after a prick by rose thorns during gardening. Clinical examination showed fusiform swelling of the finger with mild redness, warmth and fever. Blood sample revealed normal white blood cell count and a slight increase in C-reactive protein. Intraoperative observation showed extensive infectious destruction of the tendon sheath, while the flexor tendons were spared. Conventional cultures were negative, while 16S rRNA PCR-analysis identified L. longbeachae that also could be isolated on buffered charcoal yeast extract media. The patient was treated with oral levofloxacin for 13 days and the infection healed quickly. The present case report, with review of the literature, indicates that Legionella species wound infections may be underdiagnosed due to the requirement for specific media and diagnostic methods. It emphasizes the need of heightened awareness of these infections during history taking and clinical examination of patients presenting with cutaneous infections.